1976
DOI: 10.1111/j.1749-6632.1976.tb47699.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Nature of Autoimmunity in Myasthenia Gravis. Evidence for an Immunodeficiency Type*

Abstract: Clinical and laboratory data continue to support the concept of a genetically determined breakdown of immunological tolerance in myasthenia gravis with immunological damage to the motor end plates. The demonstration of impaired function of thymus-derived lymphocytes and of IgA deficiency correlate well with the clinical data in which there is an increase incidence of autoimmune diseases associated with anergy. Whilst the exact pathogenesis of myasthenia gravis is unknown, the available data support the concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
2

Year Published

1978
1978
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 40 publications
2
14
2
Order By: Relevance
“…Some investigators have found depressed responses to phytomitogens in non-thymectomized MG patients [41,45,105] whereas others [30,40,97] including ourselves [63] did not confirm this abnormality. The response to standard mitogens has been tested using indirect macrophage migration [9] and indirect leukocyte migration inhibition [35].…”
Section: Cell-mediated Immunity (Cmi)mentioning
confidence: 73%
“…Some investigators have found depressed responses to phytomitogens in non-thymectomized MG patients [41,45,105] whereas others [30,40,97] including ourselves [63] did not confirm this abnormality. The response to standard mitogens has been tested using indirect macrophage migration [9] and indirect leukocyte migration inhibition [35].…”
Section: Cell-mediated Immunity (Cmi)mentioning
confidence: 73%
“…In 1960, Simpson already pointed out that MG may be the result of an immune response to an infection, which could render the muscle protein antigenically foreign. Simpson et al [1976] showed evi dence of immunodeficiency in MG, and thought that disordered T cell function may be epiphenomena, permitting microorgan isms normally handled by the immune sys tem to circulate freely and to attack tissues for which they have a tropism. Several mech anisms for the development of autoimmune diseases following viral infection have been proposed [Hirsch and Profitl.…”
Section: Discussionmentioning
confidence: 99%
“…The thymus shows histological abnormalities in a large proportion of patients3 and there is a disturbance in the distribution of T and B cells within it.4-7 Serum IgA levels have been found to be low in 20 % of myasthenics, an abnormality commonly associated with cellular immunodeficiency. 8 Delayed cutaneous hypersensitivity reaction to 1-chloro-2-4dinitrobenzene has also been reported to be reduced. 9 Studies of the in vitro lymphocyte transformation response to phytohaemagglutinin (PHA) have yielded conflicting results, but an impaired response in myasthenia gravis has been shown in some studies.8 [10][11][12] In the previous paper, we presented evidence that myasthenia gravis is a heterogeneous disease.…”
mentioning
confidence: 99%